OPERATIONAL PERFORMANCE OF ICICI BANK - Dr. V. Sivakumar, Dr. K. Devanadhen (International Journal of Advanced Science and Technology, 2020)
The development of a country is integrally linked with the development of banking. The studymainly analyses the operational performance of ICICI Bank for the period from 2011 to 2019. Thestudy covers the key responsibility areas of deposit mobilization, credit deployment, non-performingassets, profitability and productivity. The deposit mobilization has registered growth of 289 per centand business per branch has almost quadrupled during the study period. ICICI bank intensify itsefforts to effectively and efficiently manage the NPA in the years to come, it may have to lose preciouscapital resources and eventually end up in red.